Working conditions of Social Work professionals in the Northeast region of Mexico - Lasso-Urbano, Carlos; Tamez Valdez, Blanca Mirthala (Interacción y Perspectiva, 2025)
The article examines the working conditions of graduates of the Bachelor’s Degree in Social Work in the Northeast Region of Mexico, between 2010 and 2022 for the development of strategies that contribute to professional unionization, salary demands and the demand for decent working conditions for professional prac- tice. The study was carried out from a mixed approach, for which qualitative and quantitative research techniques were applied, including surveys, documentary review and semi-structured interviews. The results obtained allow us to recognize that the working conditions of social workers in the Northeast of Mexico have been affected by precariousness, outsourcing and work overload; The main conclusions reached are that work overload predominates, the payment of salaries below the professional average, overtime work in many cases without any type of remuneration, and the growth of emotional affectation due to work overload and the multiplicity of assigned functions.